Stereoisomerism of multi-functional electrolyte additives for initially anodeless aqueous zinc metal batteries - Shengyang Huang; Hao Fu; Hyun Min Kwon; Min Sung Kim; Jun-Dong Zhang; Jun Lu; Jun Su Kim; Gun Jang; Dong Hyun Min; Won Il Kim; Guanyao Wang; Wenwu Li; et al. (Nature Communications)
Abstract Stereoisomerism, arising from the distinctive spatial arrangements of atoms despite identical molecular formulae, often displays different chemical reactivities. Herein, we demonstrate how geometric isomerism of multifunctional electrolyte additives affects aqueous zinc metal batteries. Inspired by natural bacteria, we compared trans-butenedioic acid (fumaric acid) and its cis-isomer (maleic acid), revealing different hydrogen bonding dynamics and solvation environments, as confirmed by femtosecond transient absorption spectroscopy and computational simulations. The trans-isomer promotes the formation of favorable interfacial structures and ion pathways, improving Zn deposition reversibility and cycling stability. As a result, Zn symmetric cells showed stable plating/stripping for over 6150 h at 1 mA cm−2 and 1 mAh cm−2 and 1500 h at 5 mA cm−2 and 5 mAh cm−2. The Zn-predeposited Cu||MnVO full cells exhibited a capacity retention exceeding 70% after 1000 cycles at 2 A g−1, ultimately achieving over 270 cycles for initially anodeless Cu||zincated MnVO cells at a high current density of 30 mA cm−2. The application of the isomerism concept on the design of new electrolyte materials and associated solvated and interphasial chemistries offers a new pathway to the next generation of batteries.